The influence of dynamic capabilities on strategic management accounting practices and its effect on value creation in government linked companies / Nik Herda Nik Abdullah - Nik Abdullah, Nik Herda (2017)
Value creation is an important element in every organisation to achieve business sustainability. Many organisations were reported to collapse due to the lack of management's focus in creating value in the organisation. Value creation could be developed through dynamic capabilities theory. Dynamic capabilities are the highest order capabilities that influence the development of operational capabilities and combinations of other capabilities and the related routines in business activities. From accounting perspective, value creation can be nourished by adopting strategic management accounting practices. Strategic management accounting provides management accounting information used for corporate strategic program, firm development, strategic planning and strategic control. Thus, certain types of strategic management techniques have become the focus of a majority of the research carried out. Nevertheless, limited studies investigate the influence of strategic management accounting practices and value creation within the dynamic capabilities theory. In line with dynamic capabilities, this study aims to investigate the influence of dynamic capabilities factors namely strategy formation capability, information technology capability, heterogeneity of human capital, new product development capability and alliance management capability on value creation and subsequently strategic management accounting practices in Malaysian Government Linked Companies (GLCs). GLCs contributed 54 percent of the Kuala Lumpur Composite Index and employed 5 percent of the total national workforce. Although it is evident that most GLCs have significantly contributed to the Malaysian economy, some have nevertheless shown underperformed since 1990 due to lack of value creation, weak in strategic planning, lack of capabilities, and huge gap in talent and execution skills. Data was gathered through questionnaire survey to 455 Chief Financial Officer, Chief Accountant, Chief Controller or Financial Controller of Malaysian GLCs with an interview with top management. The usable questionnaires received and used in the data analysis were 215, indicating a response rate of 47%. The structural equation modelling and SPSS were used for data analysis. The findings confirmed that dynamic capabilities namely strategy formation capability, information technology capability, heterogeneity of human capital, new product development capability, and alliance management capability have significant and positive effect on value creation and strategic management accounting practices. The results also discovered a significant positive effect between strategic management accounting practices and value creation. This study also found strategic management accounting practices plays a significant role in enhancing the relationship between strategy formation capability, information technology capability and heterogeneity of human capital on value creation. These results extend to the growing body of knowledge on strategic management accounting practices, value creation and dynamic capabilities theory as well as served as a base for future studies on strategic management accounting. Besides, it highlight the adoption of strategic management accounting practices could promotes value creation in GLCs by facilitating to improve competitiveness in the industry, upgrade financial standings, create avenues for gaining profit, business sustainability and long term performance. Thus, this study is subjected to its own limitations such as generalisation, research design and literature, which could be overcomes in future research.